Sudden deaths among Finnish conscripts. - Koskenvuo, K (1976)
The epidemiology of sudden deaths was studied among conscripts in Finland in 1948-72 (660 000 man-years) and among Finnish men aged 15-24 years in 1969-70 (900 000 man-years). The incidence of sudden deaths among the conscripts was 6-8/100 000 man-years. The onset of acute symptoms occurred during strenuous exercise in a third of the conscripts but in only a few of the other young men. Cardiovascular diseases caused two-thirds of the deaths in both groups. Sudden death tended to be more common among conscripts than among other young men during the corresponding period, but overall non-violent deaths were less common among conscripts than among other young men. On the basis of health records an attempt was made to separate the sudden deaths among conscripts from those among the controls by multiple discriminant analysis. For all practical purposes, however, the separation power proved poor.